ALIH KODE DAN CAMPUR KODE NASKAH TEKS DRAMA “KEDONDONG” KARYA ADININGSIH BANOWATI DAN BOYKE SIMATUPANG - Oegik Sri Lestariningsih; R. Panji Hermoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language as a medium of social communication continues to develop along with increasing interactions in multilingual societies that encourage the emergence of code-switching and code-mixing phenomena. These phenomena are not only found in direct communication but are also represented in literary works such as drama through character dialogues. This study aims to analyze the forms and functions of code-switching and code-mixing in the drama script Kedondong based on a sociolinguistic perspective. This research employed a descriptive qualitative method with data sources consisting of dialogues contained in the drama script Kedondong. Data collection was conducted through observation and note-taking techniques by identifying, classifying, and analyzing utterances containing code-switching and code-mixing phenomena. The results showed that code-switching appeared in the form of external code-switching through the use of English elements, while code-mixing occurred through the insertion of foreign vocabulary and informal language variations such as slang. The discussion indicated that code-switching and code-mixing function as communication strategies to strengthen expression, represent social identity, build interpersonal relationships among characters, and describe the reality of modern youth communication. This study concludes that language variation in drama scripts does not only function as a linguistic element but also represents social relationships and character construction.